Detection of tdh and trh genes in Vibrio parahaemolyticus isolated from Corbicula moltkiana prime in West Sumatera, Indonesia. - Marlina,; Radu, Son; Cheah, Yoke Kqueen; Napis, Suhaimi; Zakaria, Zunita; Abd Mutalib, Sahilah; Nishibuchi, Mitsuaki (Southeast Asian Ministers of Education Organisation, 2007)
The occurrence of Vibrio parahaemolyticus in raw Corbicula moltkiana Prime from Lake Singkarak and Pasar Raya Padang market and in cooked samples in West Sumatera, Indonesia, was studied. Thirteen raw and seven cooked bivalve samples were positive using CHROMAgar Vibrio medium. All 47 V parahaemolyticus isolates were positive for toxR gene but negative for trh. However, 36% (17/47) of V parahaemolyticus strains were positive for tdh gene. Antibiotic profiling showed that 76% and 38% of isolates from raw and cooked bivalves respectively were resistant to ampicillin. Using RAPD-PCR analysis, most of the strains were clustered according to their source of isolation but some of the strains from raw and cooked samples were clustered together. These results indicate that pathogenic V parahaemolyticus isolates are present in Corbicula moltkiana Prime in West Sumatera, Indonesia, suggesting that V parahaemolyticus may also be present in seafood in other regions of Indonesia.